2012
DOI: 10.3892/ijo.2012.1395
|View full text |Cite
|
Sign up to set email alerts
|

Kr�ppel-like factor 4 negatively regulates β-catenin expression and inhibits the proliferation, invasion and metastasis of gastric cancer

Abstract: Abstract. Krüppel-like factor 4 (KLF4) is a zinc-finger protein that plays an important role in the progression of gastric carcinoma. The abnormal activation of β-catenin frequently occurs in gastric cancer and has been associated with the promotion of tumor growth, invasion and metastasis. However, the potential interaction between KLF4 and β-catenin during gastric cancer development is unknown. In this study, a lentiviral KLF4 expression vector was constructed and utilized to transfect the human gastric canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
(67 reference statements)
3
21
0
Order By: Relevance
“…It has been reported that forced expression of KLF4 in breast tumor cell line and gastric cancer was sufficient to restore E-cadherine expression and inhibit EMT as well as suppressed migration and invasion [56], [60]. In our study, overexpression of KLF4 in spheroid cells led to a significant induction of E-cadherin, Snail as well as vimentin and deduction of ZO-1, the key mediators of EMT (Figure 7B).…”
Section: Discussionsupporting
confidence: 66%
“…It has been reported that forced expression of KLF4 in breast tumor cell line and gastric cancer was sufficient to restore E-cadherine expression and inhibit EMT as well as suppressed migration and invasion [56], [60]. In our study, overexpression of KLF4 in spheroid cells led to a significant induction of E-cadherin, Snail as well as vimentin and deduction of ZO-1, the key mediators of EMT (Figure 7B).…”
Section: Discussionsupporting
confidence: 66%
“…In GC, the function of KLF4 has been characterized as tumor suppressor and serves as a prognostic predictor for the survival of patients [18]. Overexpression of KLF4 significantly inhibited gastric cancer cell proliferation, invasion and metastatic properties [19]. This study identified KLF4 as a direct target of miR-103 in GC through dual-luciferase reporter and confirmed by western blot analysis.…”
Section: Discussionmentioning
confidence: 66%
“…KLF4 was shown to undergo promoter methylation and loss of heterozygosity in gastrointestinal cancer (119). Consistent with its tumor-suppressive function, overexpression of KLF4 reduces the tumorigenicity of colonic and gastric cancer cells in vivo (28,125). In colon cancer tissues, KLF4 levels are lower as compared with adjacent noncancer tissues and its expression is inversely correlated with the stage of tumors and survival (126).…”
Section: Roles In Diseasesmentioning
confidence: 86%